Huge Pelvic Mass, Cutaneous and Vaginal Fistulas, and Bilateral Hydronephrosis: A Rare Presentation of Actinomycosis with a Good Response to Conservative Treatment and with Long-term Sequelae of Renal Atrophy and Hydronephrosis - Pu-Tsui Wang; Shey-Chiang Su; Fang-Yu Hung; Shun-Long Weng; Chih-Ping Chen (Elsevier, 2008)
Objective: Actinomycosis with an extended pelvic abscess is an uncommon condition, which usually occurs coincident with the presence of an intrauterine contraceptive device (IUD) in the uterine cavity. The clinical picture of pelvic actinomycosis may vary between individuals, is often accompanied by complications, and is frequently misdiagnosed. Here, we report a case of pelvic actinomycosis, presenting as a huge pelvic mass and complicated by a vaginal fistula, a cutaneous fistula, and bilateral hydronephrosis, and we discuss the diagnosis and management of this patient. Case Report: A 35-year-old woman was referred to our hospital with a huge pelvic complex mass and progressively worsening low abdominal pain. The tumor workup, which included a computed tomography (CT) scan, revealed an extended pelvic abscess and bilateral hydronephrosis. Both cutaneous and vaginal fistulas were also noted. Endometrial curettage and biopsies ofthe skin and vaginal lesions confirmed the diagnosis of actinomycosis. The patient underwent conservative treatment and recovered well, although the skin lesion only healed after 1 2 weeks of oral antibiotic treatment. At the 1-year follow-up, a CTscan showed sequelae including a mildly atrophic left kidney and left hydronephrosis. Conclusion: In patients presenting with a pelvic mass and an IUD in the uterine cavity, the diagnosis of actinomycosis should be seriously considered. A detailed workup, including a CT scan, endometrial curettage and biopsies where possible, should be performed before surgery. Once diagnosis has been confirmed, conservative medical treatment should be attempted before considering laparotomy, to reduce the risk of complications. Despite successful treatment with antibiotics, long-term sequelae such as hydronephrosis and renal atrophy are possible in cases of extended pelvic actinomycosis. [Taiwan J Obstet Cynecol 2008;47(2):206-211]